Peningkatan Pendapatan Asli Desa (PAD) Melalui Pembinaan Revitalisasi Dan Tata Kelola Bumdes - Enni Savitri; Andreas Andreas; Volta Diyanto; Riska Natariasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
BUMDes is a local economics utilizing instrument with various type of potential. This potential economy is aimed improving the economics welfare of rural society through the development of economic business. Need to maximaze the role of BUMDes for increased original local government revenue. The aims of community service are to help set up the BUMDes in operation and financial reporting, strengthening the economy of the village and welfare of rural communities. The implementation of community services uses a technique of assisting the application of the BUMDes business unit management system on the Web. Community assistance with direct discussion and practice of BUMDes governance. The result of this activity is the simkeuBUMDes application. With this application, the BUMDes admin or manager is very helpful in managing BUMDes finances such as recapitulation of financial reporting BUMDes, member lists, savings members.